2017
DOI: 10.18632/oncotarget.16318
|View full text |Cite
|
Sign up to set email alerts
|

BI-RADS 3-5 microcalcifications: prediction of lymph node metastasis of breast cancer

Abstract: PurposeTo determine whether the clinicopathological parameters and Breast Imaging Reporting and Data System (BI-RADS) 3–5 microcalcifications differed between lymph node positive (LN (+)) and lymph node negative (LN (−)) invasive ductal carcinoma (IDC).ResultsFor microcalcification-associated breast cancers, seven selected features (age, tumor size, Ki-67 status, lymphovascular invasion, calcification range, calcification diameter and calcification density) were significantly associated with LN status (all P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…This is likely due to the fact that tumor sizes in the T2 group were close to the lower limit of 2 centimeters and likewise, the tumors in the T1 group were close to the upper limit of the T stage. This nding is inconsistent with a previous study which found that the rate of nodal metastases increased as the tumor size increased [24][25][26][27]. The percentage of patients with positive SLNs in the histologic grade 2 and 3 groups was higher than that in the histologic grade 1 group.…”
Section: Discussioncontrasting
confidence: 94%
“…This is likely due to the fact that tumor sizes in the T2 group were close to the lower limit of 2 centimeters and likewise, the tumors in the T1 group were close to the upper limit of the T stage. This nding is inconsistent with a previous study which found that the rate of nodal metastases increased as the tumor size increased [24][25][26][27]. The percentage of patients with positive SLNs in the histologic grade 2 and 3 groups was higher than that in the histologic grade 1 group.…”
Section: Discussioncontrasting
confidence: 94%
“…Given the wide implementation of mammography screening programs, mammographic images are available for all patients and can be used for preoperative diagnostics. Cen et al proposed a model that included age, postoperative pathological tumor size and microcalci cation density on mammographic images, resulting in a model with an AUC of 0.70 [19]. They revealed that a microcalci cation density >20 cm 2 was associated with a positive ALN status, similar to our ndings.…”
Section: Discussionsupporting
confidence: 87%
“…In this material we observed that decreasing radiologic tumor size was associated with N0 status. Pathological tumor size is a strong predictor for SLN status and often included in prediction models, although it is a postoperative variable [10,19,20]. These and previous results indicate that mammographic tumor size could replace pathological tumor size assessed from the surgical specimen as a predictor for N0 status.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Digital mammography is one of the important imaging tools for breast cancer screening and diagnosis. There have been many reports on prediction of axillary lymph node metastasis [3][4][5] and on digital mammography screening [6][7][8][9]. However, there has been no report on predicting LVI of breast cancer based on imaging patterns of digital mammography, except a little literature in which MRI findings were used for prediction [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%